BASIC PRINCIPLES TO CREATE INFORMATION SYSTEM TO MANAGE RESEARCH & DEVELOPMENT - Matrosova Н.М.; Sereda Х.В. (Journal of Information Technologies in Education (ITE), 2014)
This paper is devoted to the principles of construction of the information system of research and development management. Requirements for the development of corporate information systems for scientific research automation are described. The information system of research and development management at NAPS of Ukraine is presented. System interface and working with system documents are described.